Chitosan-based hydrogels for developing a small-diameter vascular graft: in vitro and in vivo evaluation. (3rd October 2017) - Aussel, A; Thébaud, N B; Bérard, X; Brizzi, V; Delmond, S; Bareille, R; Siadous, R; James, C; Ripoche, J; Durand, M; Montembault, A; Burdin, B; et al.
Abstract: Aims. Vascular grafts made of synthetic polymers perform poorly in small-diameter applications (cardiac and peripheral bypass). Chitosan is a biocompatible natural polymer that can provide a novel biological scaffold for tissue engineering development. The goal of this study was to demonstrate the biocompatibility of a novel chitosan preparation in vitro and in vivo, and to assess its potential as a scaffold for vascular applications. Methods and results. A series of experiments of increasing complexity, ranging from in vitro biocompatibility and hemocompatibility tests to in vivo studies in small and large animals (rats and sheep), was performed to provide a comprehensive analysis of chitosan hydrogels' biological properties. In vitro studies established that: ( i ) chitosan supported human endothelial progenitor cells adhesion, proliferation and resistance to physiological shear stress; ( ii ) chitosan did not activate platelets, the complement system, or the intrinsic coagulation pathway. In vivo results showed: ( iii ) no resorption of chitosan and no chronic inflammation at 60 days in a rat heterotopic implantation model (magnetic resonance imaging and histology); ( iv ) no flow obstruction (Doppler ultrasound) and no thrombus formation (histology and scanning electron microscopy) at 2 h after a carotid arteriotomy repair with chitosan patches in sheep. Finally, two chitosan tubes were implanted as carotid interposition grafts for 3 days in sheep showing that chitosan was strong enough to be sutured, to withstand arterial pressure, and no flow obstruction was observed through this short period. Conclusion. Chitosan-based hydrogels displayed promising in vitro biocompatibility and hemocompatibility properties as well as in vivo short-term performance.